PRINSIP DEMOKRASI DAN NOMOKRASI DI DALAM UUD RI 1945 PASCA AMANDEMEN DAN IMPLEMENASINYA DALAM STRUKTUR KETATANEGARAAN REPUBLIK INDONESIA - M. Muslih (Universitas Batanghari Jambi, 2012)
The spirit redistribute the power of the state in the 1945 Constitution after the amendment embody two major power balance. Each is the power of the people (democracy) and the rule of law (nomocracy). On the one hand, the 1945 Constitution established social ideals Indonesia to realize the power of the people as the